Smoking is a Risk Factor for Generation Z, Too: The Evolution of the Attitudes - Pavlikova, Barbara; Baska, Tibor; Freel, Lenka; Van Dijk, Jitse Pieter (International journal of public health, 2023)
Objectives: Generation Z, defined as "post-millennial," is considered to be the first generation that could end smoking. The objective is also to take into account the evolutionary aspect of the smoking and attitudes of the Generation Z. The aim of this study was to explore the willingness of Generation Z in Slovakia to comply with the legislation adopted in the field of anti-tobacco policy and to investigate some selected social factors-intention, subjective norm and percevied behavioral control-that contribute to a lower rate of compliance. Methods: Global Youth Tobacco Survey (GYTS) data on cigarette smoking among 3,557 adolescents (age range 13-15) in 2016 as well as on attitudes towards tobacco use and control measures were used to explore the level of compliance of adolescents with anti-tobacco regulations in Slovakia within the Framework Convention of Tobacco Control (FCTC). We used the concept of intention as explained in Ajzen's theory of planned behaviour (1985), focusing on the role of subjective norm and perceived behavioural control. Results: We found a decrease in ever smoking, current smoking and frequent smoking. We found that these adolescents start experimenting with dependence-causing substances, such as tobacco, regardless of existing rules. Conclusion: Adolescents were attracted to smoking, although they were aware of health effects of passive smoking, and a vast majority liked smoke-free places. They are also influenced by their peers and parental models.
Keywords: Tobacco Use; health; úmysl; tobacco products; adolescents; mladiství; FCTC; smoking; kouření cigaret; GYTS; Humans; compliance; emoce; užívání tabáku; Intention; Cigarette Smoking; rizikové faktory; Emotions; Risk Factors; Adolescent; lidé